2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944635
|View full text |Cite
|
Sign up to set email alerts
|

Towards robust HD EMG pattern recognition: Reducing electrode displacement effect using structural similarity

Abstract: Even small changes of electrode recording sites after training a classifier heavily influence robustness and usability of traditional pattern recognition-based myoelectric control schemes. This effect occurs during donning and doffing of the prosthesis or when changing the arm position and generally leads to a significant decrease of classification accuracy. On the other hand, image representations taken from high density electromyographic (EMG) signals offer high spatial resolution and only seem to change sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The most commonly reported limb position experimental protocol in the literature is one that uses static limb positions [21,22,94,[113][114][115][116]119,[121][122][123][126][127][128][129][130][131][132][133][134][135][136][137][138]. Among the articles surveyed, these make up 50% of all experiments.…”
Section: Static Limb Positionmentioning
confidence: 99%
“…The most commonly reported limb position experimental protocol in the literature is one that uses static limb positions [21,22,94,[113][114][115][116]119,[121][122][123][126][127][128][129][130][131][132][133][134][135][136][137][138]. Among the articles surveyed, these make up 50% of all experiments.…”
Section: Static Limb Positionmentioning
confidence: 99%
“…The most common experimental procedure consists of training the classifiers on features extracted from the original signals and testing the classifier on features from the shifted signals. The maximum electrode displacement distance that is likely to occur in the normal everyday use of the prosthetic hand is noted in different studies as 1 cm (Hargrove et al, 2008 ; Boschmann and Platzner, 2012 , 2014 ; Muceli et al, 2014 ; Pan et al, 2015 ; Stango et al, 2015 ).…”
Section: Causes Of Emg Variability With Timementioning
confidence: 99%
“…The detection of electrodes shifts from their original positions does not follow a physiological pattern that can be described by ME signal characteristics as in the case of muscle fatigue. Most studies rely on indirectly detecting the electrode shift by monitoring either the classification accuracy or the classification error (Hargrove et al, 2008 ; Tkach et al, 2010 ; Boschmann and Platzner, 2012 , 2014 ; Young et al, 2012 ; Pan et al, 2015 ; Stango et al, 2015 ). A decrease in the former or increase in the latter is associated with some disturbance in the EMG signals, that is not necessarily uniquely associated with electrode shift and could be the result of other disturbances (see following sections).…”
Section: Causes Of Emg Variability With Timementioning
confidence: 99%
See 1 more Smart Citation
“…However, increasing the number of electrodes also increases the processing involved, and it has already been shown that the increase in the performance of an EMG classifier isn't significant after four electrodes [4]. Other way to tackle the problem would be using more robust classifiers that can withstand changes in the signal [1 and 5], or even training the classifier with the electrodes slightly shifted [2]. But none of these approaches were consolidated as satisfactory.…”
Section: Introductionmentioning
confidence: 99%